Mathematical modeling and vaccination acceptability analysis of COVID-19 in Nigeria - Gambo Adamu; Mohammed Ibrahim; Catherine Ejieji; Hussaini Bazata Yusuf (Mathematics and Computational Sciences, 2021)
Abstract: The novel coronavirus 2019 known as (COVID-19) pandemic caused by SARS-CoV-2 occurred in Wuhan town of China in 2019. The virus has rapidly spread all over the world and has continued to affect the public well-being. This paper focuses on a mathematical model with vaccination acceptability of COVID-19 with which to examine to what extent the vaccine would be accepted in Nigeria. Specifically, the paper introduces a compartmental model to measure the potential impact of the COVID-19 vaccine. The vaccination acceptability model results show that up to 80% of the Nigerian populace accepted the vaccination campaign, despite the gabs on the COVID-19 vaccine by some health workers and the communities in Nigeria. It also shows that 90% vaccinated susceptible plus 50% effectiveness of face-mask use has brought about a decrease of the pandemic while mortality rate has decreased drastically which shows that the vaccine is effective. The result also reveals that the recovered individuals from COVID-19 have increased in alignment and, the vaccine has a significant impact on the populace. Finally, possible extensions of the model as well as open challenges associated with the formulation and analysis of COVID-19 dynamics will be addressed.